Fibroscan detection of fatty liver and liver fibrosis in patients with systemic lupus erythematosus. (May 2022) - Yetginoglu, Ozge; Atas, Dilek Barutcu; Yilmaz, Yusuf; Velioglu, Arzu; Arikan, Hakki; Alibaz-Oner, Fatma; Direskeneli, Haner; Tuglular, Serhan; Asicioglu, Ebru
Objective: Although liver dysfunction is not considered the main organ involvement in Systemic Lupus Erythematosus (SLE), the frequency of liver dysfunction or abnormal liver enzyme values may be observed in 50–60% of patients. The aim of this study was to assess fatty liver and liver fibrosis in SLE patients using Fibroscan as well as determine associated factors such as immunosuppressive medications. Methods: Sixty SLE patients and 30 healthy controls were included. Patients with HBV, HCV or cirrhosis, malignancy, cardiac disease, or patients on dialysis were excluded. All participants underwent Fibroscan measurements. Results: The prevalence of fatty liver disease was similar between SLE patients and healthy controls (21.7 vs 26.7%, p = .597). Liver fibrosis was also similar between the two groups (26.7 vs 10.0%, p = .069). Since the majority of SLE patients were female, we performed a subgroup analysis in female patients ( n = 51) and controls ( n = 25). Fatty liver disease was similar between female SLE patients and controls (23.5 vs 24.0%, p = .964). However, liver fibrosis in female patients with SLE was increased compared to female controls (29.4 vs 4.0%, p = .011) and was associated with age (Exp (B) 95% CI: 1.083 (1.006–1.166), p = .034) and low-dose cumulative glucocorticoid use (Exp (B) 95% CI: 14.116 (1.213–164.210), p = .034). Conclusion: The prevalence of fatty liver was similar between SLE patients and controls, while liver fibrosis was increased in the female patient group as compared to controls. Furthermore, liver fibrosis was associated with age and low dose cumulative glucocorticoid use. Interestingly, fatty liver did not precede liver fibrosis in the majority of cases, contrary to what is observed in the general population. Larger studies are needed to confirm our findings and determine whether immunosuppressive use has any impact on the development of liver fibrosis in SLE patients.